ANALISIS KINERJA KEUANGAN PT. SAT NUSA PERSADA. TBK PERIODE 2015-2019 - Coryne Jessa; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The development of the printed circuit board (PCB) supplier industry, assembling mechanical parts and assembling electronic components, does not rule out the possibility that PT. Sat Nusapersada. Tbk. In addition, companies must have good financial performance, so they can survive in the computer component industry. Therefore, it is important to assess the company's financial performance. The purpose of this research is to analyze the financial performance of PT. Sat Nusa Persada. Tbk period 2015-2019. The method used in writing this research is descriptive quantitative. The type of data used in this study is quantitative data. Meanwhile, when viewed from the data acquisition, the data in this study is secondary data. The data collection technique in this study is a documentation technique. Data analysis technique is quantitative by using . Financial ratios are ratios of liquidity, profitability, solvency and activity. This study shows that: First: The condition of liquidity ratios, Solvency Ratios (Leverage Ratios), Activity/Efficiency Ratios (Activity Ratios), Profitability Ratios (Profitability Ratios), fluctuates, of course as a result of company policies, especially related to the use of current assets, and also company loans. in 2018, which triggered an increase in the company's entire financial ratios. Keywords: Liquidity ratios, Solvency Ratios (Leverage Ratios), Activity Ratios (Activity Ratios), Profitability Ratios (Profitability Ratios)